2014
DOI: 10.2106/jbjs.m.00271
|View full text |Cite
|
Sign up to set email alerts
|

Improved Chondrogenic Capacity of Collagen Hydrogel-Expanded Chondrocytes

Abstract: The study results favor the use of hydrogel-expanded cells over the traditional plastic-expanded cells for autologous chondrocyte implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…These results concur with those from our earlier research, in which we suggested that Alk-1 and Alk-5 are suitable candidates for the final effector of the response of chondrocytes to changes in substrate rigidity [8]. These two transmembrane proteins function as opposite receptors for TGFβ [19].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results concur with those from our earlier research, in which we suggested that Alk-1 and Alk-5 are suitable candidates for the final effector of the response of chondrocytes to changes in substrate rigidity [8]. These two transmembrane proteins function as opposite receptors for TGFβ [19].…”
Section: Discussionsupporting
confidence: 93%
“…The average ± SD for every group (n = 6) is represented for passages 0, 2, 4, 6 and 8. D -We also used wildtype chondrocytes cultured onto hydrogels to which peptide was added after passage 4, when the cells had shown to increase the expression of Alk-1 receptor [8] and it would be desirable to inhibit TGFβ activity. *p < 0.05 for peptide-treated cells relative to the control cells in every passage.…”
Section: Inhibition Of Tgfβ In Hydrogel-cultured Alk-5 and Sh-alk-1 Cmentioning
confidence: 99%
See 3 more Smart Citations